KEPADATAN POPULASI DAN NISBAH KELAMIN IKAN BUTUH KELENG (Butis butis) DI SUNGAI BELAWAN - Helentina Mariance Manullang; Khairul Khairul (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
Belawan River stores a fairly high diversity of fish, one of which is the crazy fish (Butis butis). A study of the bioecology of crazy fish has not done in Indonesia. They are considering the lack of bioecology of this fish in Indonesia. At the same time, bioecology data is needed by various parties as data and important information to know the condition of the fish population in nature. The purpose of this research is to know the population density and genital ratio of fish need keleng in Belawan River. This research is exploration. The location of fish sampling used a purposive sampling method.  Fish arrested one time each month using a fishing rod. The collected fish are taken in total length and weight and identified the type of gender. Processing data using the application program Microsoft Excel 2010. The results showed the population density of fish at Station 1 (0.91 individual/m2), Station 2 (0.92 individual/m2, and station 3 (0.35 individual/m2). Sex ratio at Station 1, male fish (66%) and female (34%), Station 2, male fish (50,60%) and females (49,40%) and Station 3, male (50,77%) and females (49,23%).